THE LANGGA PRACTICE IN THE RABA-RABA PURU TRADITION OF BENDUNGAN VILLAGE, MANANGGU DISTRICT, BOALEMO REGENCY, GORONTALO PROVINCE, INDONESIA - Abd. Rahman Paudi; Resmiyati Yunus; Naufal Raffi Arrazaq; Irvan Tasnur (Satmata: Journal of Historical Education Studies, 2026)
This study aims to explore the meaning, process, and cultural values embedded in the Langga tradition practiced during the raba-raba puru ceremony in Bendungan Village, Mananggu Sub-district, Boalemo Regency, Gorontalo Province. The tradition is performed during the seventh month of pregnancy as an expression of ancestral reverence and a prayer for maternal and fetal well-being. This research employs a qualitative approach through in-depth interviews, participatory observation, and field documentation. Findings reveal that although the philosophical meaning is not entirely understood by the community, the tradition is preserved due to its deep-rooted social and spiritual values. The ritual includes symbolic elements such as cloth, offerings, and traditional tools that represent protection and hope. Langga also strengthens community solidarity, reinforces the role of cultural leaders, and serves as a medium for intergenerational cultural education. Amid the pressures of modernization, preserving this tradition requires a community-based adaptive approach. Thus, Langga stands not only as a cultural legacy of the past but also as a source of enduring values for the future of the local society.